Self-directed training with e-learning using the first-person perspective for laparoscopic suturing and knot tying: a randomised controlled trial - Schmidt, Mona Wanda; Kowalewski, Karl-Friedrich; Trent, Sarah; Benner, Laura; Müller, Beat P.; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2020)
Laparoscopic suturing and knot tying is essential for advanced laparoscopic procedures and requires training outside of the operating room. However, personal instruction by experienced surgeons is limitedly available. To address this, the concept of combining e-learning with practical training has become of interest. This study aims to investigate the influence of the first-person perspective in instructional videos, as well as the feasibility of a completely self-directed training curriculum for laparoscopic suturing and knot tying.
Published online: 28 May 2019
Gesehen am 09.03.2020